A Method to Specify Requirements for A Hospital Management Software - Mohammad Shahadat Hossain; Md. Abdul Halim; Md. Masudur Rahman; Khorshed Alam (Indonesian Management and Accounting Research, 2006)
The diagnosis of disease and the treatment, both medical and surgical, to the sick and injured people are the main role of a hospital as an institution. To achieve these objectives hospital is built in a suitable location, staffed with skilled manpower and equipped with the state of the art modem medical technologies. Nowadays, hospital as an institution is becoming an example of complex system because of the existence of increasing diverse interrelationships among its various entities/components. The management of the hospital, which is mainly manually operated, is unable to cope with this increasing diversification of the interrelationships and the information resulting form them. A computer-based information system (CBIS), which has the ability to handle large amount of information and their interrelationships in an organisation can be seen as an appropriate solution at this point. The development of an effective CBIS is not a straightforward task. This consists of a series interrelated stages such as requirement specification, system design, implementation and maintenance. Among them requirement specification is considered as the most important stage, since the viability of a CBIS mainly depends on it. Therefore, the paper presents the procedures of capturing requirement specifications for the CBIS to be used in a hospital. This can be demonstrated that the specifications in turn will enable an understanding of all aspects of the system in a consistent and coherent way and therefore to define its boundary.Keywords: CBIS, System, Requirement Specifications, Hospital and Problem Domain